Cloning and Expression of ORF124 Koi Herpesvirus as a Vaccine - M. Murwantoko; Dewi Nur'aeni Setyowati; Rarastoeti Pratiwi; Masashi Kawaichi (Universitas Gadjah Mada, 2012)
Koi herpesvirus (KHV) which also known as Cyprinid herpesvirus 3 (CyHV-3), Koi herpes-like virus,and carp interstitial nephritis gill necrosis virus (CNGV), caused signifi cant morbidity and mortality in koiand common carp (Cyprinus carpio). The case fatality rate of this disease is 80–100%. Glycoprotein has beenused for vaccine development as sub unit vaccine against viruses. The aim of this research was to clone andexpress membrane glycoprotein ORF124 KHV as a candidate of recombinant vaccine. ORF124 KHV gene wassuccessfully cloned into pBSKS and sequenced. Result showed that ORF124 KHV (isolate from Indonesia) had100 % similarity with Cyprinid herpesvirus 3 strain TUMST1 (from Japan), 99% similarity with Koi herpesvirus strain KHV-U (from USA) and Koi herpesvirus strain KHV-I (from Israel). Prediction analysis of T and B cellepitopes showed that ORF124 KHV protein had 14 and 11 T cell epitopes (IAd, Rothbard/Taylor pattern),and had 10 B cell epitopes, suggested that the protein can be used as a vaccine candidate. ORF124 gene hasbeen expressed in Escherichia coli under pET32-a(+)vector.